The Effect of Addition Star Fruit Juice (Averrhoa Bilimbi L.) with Different Concentrations and Lengths of Soaking Time Against Decay of Vaname Shrimp (Litopenaeus Vannamei) - Rosmaidar Rosmaidar; Rastina Rastina; Nurliana Nurliana; Hennivanda Hennivanda; Azhari Azhari; Putri Distyana Yolanda (The International Journal of Tropical Veterinary and Biomedical Research, 2023)
One of the fishery products that decomposes very rapidly is shrimp. Utilizing natural preservatives, such as Averrhoa bilimbi L. juice, is one method for maintaining the quality of food ingredients. This study aims to determine the effect of adding A. bilimbi L. juice with different concentrations and soaking times on vannamei shrimp decay. In this study, an experimental laboratory was used to examine decay using the Postma and H2S tests. As much as 500 g of vannamei shrimp were divided into four treatment groups and two repetitions, with 5 g of each sample soaked in A. bilimbi L. juice with concentrations of 0%, 2.5%, 5%, 7.5%, and 10% for 0, 3, 6, and 9 hours. Early decay was observed at 0 and 3 hours after soaking vannamei shrimp in solutions with concentrations of 0%, 2.5%, 5%, 7.5%, and 10%. At concentrations of 5%, 7.5%, and 10%, there was no initial decay after soaking vannamei shrimp for six hours at a concentration of 0% and 2.5%. During 9 hours of soaking at concentrations of 0%, 2.5%, and 5%, initial decay occurred, whereas there was no initial decay at concentrations of 7.5% and 10%. The conclusion of this research is A. bilimbi L. juice with concentrations of 7.5% and 10% for 6 and 9 hours inhibits the decomposition of vannamei shrimp.